Study on crack interaction effect of API steel using finite element analysis - Ahmad Syauqi Fathuddin, Md Shaimi (2012)
This project is a study on crack interaction effect of API steel using Finite Element Analysis (FEA). The objectives for this project are to study the interaction of two noncoplanar cracks and analyze the maximum stress for various crack size and pressure on defect. This project involves analysis of the API X65 steel by using MSC Marc 2008 r1 software. This analysis investigates two failure criterions that are maximum shear stress and von Mises stress. The model was prepared by using MSC Marc 2008 r1 and only in quarter of the pipe while simulated and analyzed in 2D dimension. The model of quarter pipe with the diameter outer diameter 610 mm and 15.8 mm thickness were simulated to analyze the crack. The maximum stress occurred at the internal tips of the cracks because this stresses are higher than at the external tips. The interaction of the stress field of two approaching non-coplanar pressurized cracks will be higher, and therefore will produce higher stresses, as the cracks become of similar size.